Using Design-Based Research to Develop Innovation in Open University in Thailand - Chanyawudhiwan, Gan; Mingsiritham, Kemmanat (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This paper discusses Design-Based Research (DBR) used to develop an innovation in a distance university. The innovation focuses on self-study through technology. It has results in 3 aspects which are 1) Instructors can assess knowledge and prepare the content from both internal and external learning sources in accordance with students’ needs, 2) Students can analyze their ability in order to plan successful online learning by themselves, and 3) Instructional designers can analyze, plan, design activities and select learning resources in accordance with the content and learning behavior. This paper describes the concept of DBR with the sample of "STOU Smartlearn" innovation design which is a smart evaluation system of Sukhothai Thammathirat Open University (STOU). The innovation was designed based on DBR process. It has been used with students and could be modified to suit students’ needs. The results of the two experiments with undergraduate students in the academic year 2018 and 2019 found that the effect size increased from .27 to .32.